Optimization of the MESH network route by means of an artificial neural model - Safonyk, Andrii; Mishchanchuk, Maksym; Lakus, Petro (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2020)
This article about system of remote-control access to the rooms and buildings based on MESH network. On MESH network for make routes used neural network developed by Tensorflow and Keras